2021
DOI: 10.1086/708913
|View full text |Cite
|
Sign up to set email alerts
|

Ex Post Review and Expert Policy Making: When Does Oversight Reduce Accountability?

Abstract: Ex post review is a common feature of policymaking institutions. We consider an environment in which an expert agent makes a policy recommendation, which can then be accepted or rejected by an overseer whose policy goals differ from those of the agent. The theory suggests that both behavior and optimal institutional design are sensitive to several factors, including actors' preference alignment, the importance of the policy decision, and the uncertainty about the correct policy choice. We characterize the type… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In that sense, the bureaucracy would be (potentially) constrained by the threat of a fire alarm alerting the president or Congress—or both—of agency subversion regardless of policy instrument (McCubbins and Schwartz ). Similarly, explicit incorporation of judicial review is a promising extension, as previous work has shown the presence of effective judicial review can have profound impacts on bureaucratic policy‐making incentives, both positive and negative (Bueno de Mesquita and Stephenson ; Gailmard and Patty ; Patty and Turner, forthcoming; Shipan ; ; Turner ; ). This may be particularly interesting because judicial oversight is separate from consideration of the ability of Congress or the president to monitor while also bargaining over policy.…”
Section: Discussion: Extending the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In that sense, the bureaucracy would be (potentially) constrained by the threat of a fire alarm alerting the president or Congress—or both—of agency subversion regardless of policy instrument (McCubbins and Schwartz ). Similarly, explicit incorporation of judicial review is a promising extension, as previous work has shown the presence of effective judicial review can have profound impacts on bureaucratic policy‐making incentives, both positive and negative (Bueno de Mesquita and Stephenson ; Gailmard and Patty ; Patty and Turner, forthcoming; Shipan ; ; Turner ; ). This may be particularly interesting because judicial oversight is separate from consideration of the ability of Congress or the president to monitor while also bargaining over policy.…”
Section: Discussion: Extending the Modelmentioning
confidence: 99%
“…The agency is a nonstrategic player in the sense that I assume that it cannot move the spatial location of policy; it only invests in quality as a function of costs cq, which are further dependent on the agency’s capacity λ. Of course, one can easily adapt the model to incorporate other important considerations, such as bureaucratic discretion (Epstein and O’Halloran ; ), interbranch oversight (Epstein and O’Halloran ; Patty and Turner, forthcoming), or differential policy complexity (Callander ; McCarty ). I discuss several such possibilities in the discussion section below.…”
Section: A Model Of Unilateral Action With Bureaucracymentioning
confidence: 99%
“…Our theme is related to but distinct from the oversight of public agencies by specialized overseers, like the judiciary, the US Office of Information and Regulatory Affairs, and similar specialized bodies. There is a growing literature focusing on this topic (see Almendares and Le Bihan, 2015;Stephenson, 2011, 2015;Patty and Turner, 2020;Turner, 2017: among many others). Unlike in our model, in this literature either the supervised agency and/or the overseer are non-elected bodies.…”
Section: Related Literaturementioning
confidence: 99%
“…More broadly, recent work on political principal–agent settings has explored various limits to oversight, particularly exploring mechanisms by which principals' oversight activities may distort agents' incentives in ways that are undesirable to the principal. See, for example, Canes‐Wrone, Herron, and Shotts (), Fox (), and Fox and Stephenson () in the electoral context; Turner (, n.d.) in a bureaucratic setting, Hübert () in the trial/appellate court setting; and Patty and Turner (n.d.) in a generic oversight context. In parallel, some work has focused on settings of competitive valence , where multiple agents compete to design rules or policies that will be chosen by a principal (Hirsch and Shotts ; Hitt, Volden, and Wiseman ; Lax and Cameron ); in this work, the focus is more on rule design per se than oversight.…”
Section: Related Literaturementioning
confidence: 99%